Comprehensive Analysis Identifies Ameloblastin-Related Competitive Endogenous RNA as a Prognostic Biomarker for Testicular Germ Cell Tumour - Tianxiang Geng (Cancers, 2022)
Testicular Germ Cell Tumour (TGCT) is one of the most common tumours in young men. Increasing evidence shows that the extracellular matrix has a key role in the prognosis and metastasis of various human cancers. This study analysed the relationship between the matrix protein ameloblastin (AMBN) and potential biological markers associated with TGCT diagnosis and prognosis. The relationship between AMBN and TGCT prognosis was determined by bioinformatic analysis using the expression profiles of three RNAs (long non-coding RNAs (lncRNAs), microRNAs (miRNAs) and mRNAs) from The Cancer Genome Atlas (TCGA) database, and available clinical information of the corresponding patients. Prediction and validation of competitive endogenous RNA (ceRNA) regulatory networks related to AMBN was performed. AMBN and its associated ceRNA regulatory network were found to be related to the recurrence of TGCT, and LINC02701 may be used as a diagnostic factor in TGCT. Furthermore, we identified PELATON (Plaque Enriched LncRNA In Atherosclerotic And Inflammatory Bowel Macrophage Regulation) as an independent prognostic factor for TGCT progression-free interval.